Transcriptional Mechanism of Jasmonate Receptor COI1-Mediated Delay of Flowering Time in Arabidopsis. Issue 10 (28th September 2015) - Zhai, Qingzhe; Zhang, Xin; Wu, Fangming; Feng, Hailong; Deng, Lei; Xu, Li; Zhang, Min; Wang, Qiaomei; Li, Chuanyou
Abstract : Underlying the jasmonate receptor COI1-mediated delay of flowering, the APETALA2 transcription factors TOE1 and TOE2 interact with a subset of JAZ repressors to regulate the expression of FT. Abstract: Flowering time of plants must be tightly regulated to maximize reproductive success. Plants have evolved sophisticated signaling network to coordinate the timing of flowering in response to their ever-changing environmental conditions. Besides being a key immune signal, the lipid-derived plant hormone jasmonate (JA ) also regulates a wide range of developmental processes including flowering time. Here, we report that the CORONATINE INSENSITIVE1 (COI1)-dependent signaling pathway delays the flowering time of Arabidopsis thaliana by inhibiting the expression of the florigen gene FLOWERING LOCUS T ( FT ). We provide genetic and biochemical evidence that the APETALA2 transcription factors (TFs ) TARGET OF EAT1 (TOE1) and TOE2 interact with a subset of JAZ (jasmonate-ZIM domain) proteins and repress the transcription of FT . Our results support a scenario that, when plants encounter stress conditions, bioactive JA promotes COI1-dependent degradation of JAZs. Degradation of the JAZ repressors liberates the transcriptional function of the TOEs to repress the expression of FT and thereby triggers the signaling cascades to delay flowering. Our study identified interacting pairs of TF and JAZ transcriptional regulators that underlie JA -mediated regulation of flowering, suggesting that JA signals are converted into specific context-dependent responses by matching pairs of TF and JAZ proteins.